Multidimensional tropical forest recovery - Pooter, Lourens; Craven, Dylan; Jakovac, Catarina C; van der Sander, Masha T; Amissah, Lucy; Bongers, Frans; Chazdon, Robin L; Farrior, Caroline E; Kambach, Stephan; Meave, Jorge A; Muñoz, Rodrigo; Norden, Natalia; et al. (AAAS, Washington, DC (USA), 2021)
Tropical forests disappear rapidly because of deforestation, yet they have the potential to regrow naturally on abandoned lands. We analyze how 12 forest attributes recover during secondary succession and how their recovery is interrelated using 77 sites across the tropics. Tropical forests are highly resilient to low-intensity land use; after 20 years, forest attributes attain 78% (33 to 100%) of their old-growth values. Recovery to 90% of old-growth values is fastest for soil (<1 decade) and plant functioning (<2.5 decades), intermediate for structure and species diversity (2.5 to 6 decades), and slowest for biomass and species composition (>12 decades). Network analysis shows three independent clusters of attribute recovery, related to structure, species diversity, and species composition. Secondary forests should be embraced as a low-cost, natural solution for ecosystem restoration, climate change mitigation, and biodiversity conservation.